Ontogênese comportamental de Callithix jacchus em ambiente natural - Lima, Ana Karinne Moreira de (2010)
In most primates, the mother is primarily responsible for care in early life of the infants, since, as in other mammals, infants depend on their mother to nutritional conditions. However, unlike most of them, in some species, infants are also dependent on other individuals with respect to transportation, supervision, and food sharing. To understand the distribution of care to offspring is essential to understand the social dynamics of the group. Several studies conducted in the natural environment, during the infant have been studied mainly through the careful transport of the infants. Our study approached the different forms of care to infants (transport, supervision and food sharing) and the development of behavioral repertoire throughout all phases of infant and juvenile seeking to better understand how to establish the development and survival of offspring of Callithrix jacchus, in natural environment. The seasonality in the caatinga was striking in this study and the collection had two distinct seasons for each of the sets observed, one dry and one rainy. These environmental changes seem to have influenced the distribution of activities in animal development. Yet the greater availability of resources in the rainy season seems to have been the main factor influencing the pattern of activities. Results will be presented in two manuscripts